PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS-ACHIEVEMENT DIVISION (STAD) TERHADAP MOTIVASI DAN KEMANDIRIAN BELAJAR PADA ROTASI GARIS YANG BERPUSAT DI KELAS XI SMA NEGERI 3 PAMEKASAN - Awaluddin; Muhajir; Huda, Nuril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In learning activities, various teaching methods are applied by teachers for the success of learning. As for learning, a teacher also needs to know the characteristics of his students. What we need to know is that each student has different characteristics. So it is certain that a teacher examines and re-examines teaching methods before applying them to students. One learning model that can be used in mathematics learning is to determine the influence of motivation and learning independence from cooperative learning using the Student Teams-Achievement Division STAD type and comparing two learning models, namely the STAD type cooperative learning model with those taught not using Student Teams-type cooperative learning. Achievement Division STAD or learning that is commonly carried out by teachers, namely in this case the learning that we know as conventional learning. This is intended to determine whether there is/isn't a significant difference in the motivation and independence of those taught using Student Teams-Achievement Division STAD type cooperative learning with learning achievement taught not using Student Teams-Achievement Division STAD type cooperative learning or conventional learning. From the research results, the results of the questionnaire stated that in the independent t-test using SPSS 21 for Windows, student learning motivation was obtained at 0.03, which is smaller than the t-table of 0.05 and for learning independence, it was obtained at 0.04, which is also smaller than in t-table 0.05. From this description it can be concluded that the sig. (2-tailed) is smaller than 0.05 for learning motivation, which is 0.003, smaller than 0.005, meaning that the use of Student Teams-Achievement Division (STAD) type cooperative learning is effective in increasing student learning motivation in line rotation centered at (a, b) Class XI Pamekasan 3 Public High School. Meanwhile, learning independence is 0.004, smaller than 0.005. So we can conclude that the use of cooperative learning of the Student Teams-Achievement Division (STAD) type is effective in increasing student learning independence in line rotations centered at (a, b) Class XI SMA Negeri 3 Pamekasan